"Do you dare to go to the square?" The legacy of Soviet dissidents in Russian public protests of the 2000s and 2010s. Issue 3 (3rd May 2020) - Kozlov, Dmitry
ABSTRACT: This paper analyzes the mechanisms of creating a symbolic connection between several generations of protesters in the late USSR and in Putin's Russia. Based on an analysis of the periodical press, data on human-rights violations during public protests, and published sources on the history of Soviet dissidents, the article traces how and for what purposes protesters in the 2000s and 2010s used the symbolic and practical legacy of Soviet dissidents, what additional meanings of protest were actualized with these linkages, and how references to specific spaces of protest actions transformed the content and form of public protests. Using Charles Tilly's concept of "repertoires of contention, " I argue that references to the dissidents' legacy were not limited to the discursive level of repeating slogans but included various public actions that memorialized and/or reconsidered the Soviet dissidents' tradition of contesting the state monopoly over public space.